Handbuch IQM Konsequent transparent - Qualität mit Routinedaten! 3. Auflage - Martin, Jörg; Braun, Jan-Peter; Zacher, Josef (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2023)
To date, more than 500 member hospitals from Germany and Switzerland are committed to more quality in medical and nursing care in the Quality Medicine Initiative (IQM). The IQM quality methodology uses quality measurement from routine data, consistent internal and external result transparency and, with the IQM peer review process, offers a network for continuous quality improvement. The IQM handbook explains the goals of IQM. Valuable practical tips and working materials support the readers in the implementation and sustainable application of the IQM quality methodology and thus in the creation of an open error and improvement culture in their own hospital. In addition, the new edition of the manual contains additional content that shows how IQM is developing beyond the actual methodology. Articles on current topics, such as coping with the COVID-19 pandemic, complement the handbook.